Knowledge, attitude and practice on hand, foot, and mouth disease (HFMD) among caregiver of five years old children / Mohammad Nasir Abdullah ... [et al.] - Abdullah, Mohammad Nasir; Najmuddin, Ahmad Farid; Zuraimi, Norhafizzah; Mohd Muzi, Nur A’fini; Mohd Nadzir, Nur Aisyah; Shamsul Kamal, Nuramanina Husna; Bohari, Muhammad Akmal Hakim (Universiti Teknologi MARA, Perak, 2019)
Hand, foot and mouth disease (HFMD) is caused by a group of viruses known as enteroviruses which is coxsackievirus A16 (CA16) and enterovirus A71 (EV-A71). These viruses are the common causes of HFMD. The public usually recognized HFMD as infection to the children. This report describes knowledge, attitude, and practice on HFMD among caregiver of five years old children. Knowledge, practice, and attitude of caregivers towards this disease are important factors to prevent the outbreak of HFMD for children. The aim of these study was to investigate knowledge, attitude and practice towards HFMD among caregivers of children, especially at childcare centers. At Kinta, the district of Ipoh, 314 children (81.77%) have not been infected with HFMD while the remaining 70 children (18.23%) have experience with HFMD. By using multiple linear regression analysis, there were two important factors that contribute to respondent’s practice which were Knowledge score and Attitude score. There was a significant linear relationship between practice score and knowledge score (adjusted b= 0.33795; 95% CI = (0.2154, 0.4605); p-value = 0.001). Next, there was a significant linear relationship between attitude score and practice score (adjusted b= 0.16664; 95% CI = (0.0759, 0.2573); p-value < 0.001). The findings also show that the caregivers’ knowledge needs to be improved, as well as their preventive attitude and behavior on HFMD. The caregivers need to take care of their children and pay more attention to this infection.